2020
DOI: 10.3390/pharmaceutics12100947
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oil-in-Water Self-Emulsifying Microemulsion for Cutaneous Delivery of Rose Bengal: Investigation of Anti-Melanoma Properties

Abstract: The topical delivery route is proposed as an alternative or adjunctive approach to melanoma treatment, since the target site for melanoma treatment—the epidermal basal layer—is potentially accessible by this route. Microemulsion systems are effective delivery vehicles for enhanced, targeted skin delivery. This work investigated the effect of Rose Bengal (RB) and RB-loaded self-emulsifying microemulsions (SEMEs) on growth inhibition of human melanoma and normal skin cell monolayers, the safety of the excipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 51 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…Because the number of parameters was not identical for each model, and R 2 increases with increasing numbers of parameters, for the selection of the mathematical model which fits best on the experimental data, it was necessary to use the adjusted correlation coefficient (R 2 adj ) [ 56 , 57 ]. This formula was used: R 2 adjusted = 1 − (( n − 1) × (1 − R2))/( n p − 1), where “p” is the number of parameters in the model and “ n ” is the number of experimental data points [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Because the number of parameters was not identical for each model, and R 2 increases with increasing numbers of parameters, for the selection of the mathematical model which fits best on the experimental data, it was necessary to use the adjusted correlation coefficient (R 2 adj ) [ 56 , 57 ]. This formula was used: R 2 adjusted = 1 − (( n − 1) × (1 − R2))/( n p − 1), where “p” is the number of parameters in the model and “ n ” is the number of experimental data points [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“… 63–66 In the case of RB, increased cellular uptake seems to be critical for phototoxic activity: regardless of the level of singlet oxygen generation, RB-loaded dendrimersomes generate significantly higher levels of intracellular ROS, which translates into a stronger phototoxic effect. The IC 50 values for RB-loaded dendrimersomes in vitro are remarkably low (~1 µM RB for both formulations), considerably lower than those for most formulations mentioned above (for instance 28 , 30 , 32 , 36 ). Importantly, the dark toxicity of RB-loaded dendrimersomes is negligible in the concentration range used.…”
Section: Discussionmentioning
confidence: 61%
“…The IC 50 values of K. galanga rhizome oil and microemulsion were 6.8 mg/mL and 0.6 mg/mL, respectively. A previous study reported IC 50 values of 100.60 μg/mL, 83.04 μg/mL, and 94.75 μg/mL for ethyl-cinnamate, ethyl-p-methoxy-cinnamate, and trans-cinnamaldehyde, respectively [ 37 ] These results suggested that the microemulsion enhanced the cytotoxicity of K. galanga rhizome oil to RAW 264.7 cells, which was probably due to the enhancing solubility and penetration of the oil through the cell membrane via the surfactant of the microemulsion [ 38 , 39 , 40 ]. The cytotoxicity criteria of K. galanga rhizome oil, microemulsion containing oil, and blank microemulsion against RAW 264.7 cells conformed with ISO 10993–5:2009, which describes that reduction of cell viability by more than 30% is considered a cytotoxic effect.…”
Section: Resultsmentioning
confidence: 99%